A decision support model to aid the management of crises in urban water supply systems (the UWC-MODEL). Issue 6 (3rd July 2017) - da Silva, Welitom T. P.; Souza, Marco A. A.
Abstract: The objective of this study was to develop a model for crisis management in urban water supply systems, able to assist the decision-making process to deal with the urban water crisis (UWC) by those responsible for these systems. The research methodology used for model development consisted of the following steps: (1) development of a decision support model for cases of crises in urban water supply systems (UWC-MODEL); (2) performing the sensitivity analysis of the UWC-MODEL; (3) verifying the UWC-MODEL; and (4) application of the UWC-MODEL. Different levels (socio-economic, management, urban, environmental and cultural) of the UWC problem were considered in the UWC-MODEL. It was based on the similarity between a weak UWC situation (or absence), strong UWC situation (or severe) and the actual case. Results of the application of the UWC-MODEL to the Administrative Region of Brasilia, in the Federal District of Brazil, indicated that actions related to cultural and environmental levels demonstrated a greater contribution for combating UWC. Actions such as environmental education programs, water conservation programs, and use of water saving equipment, were indicated by the UWC-MODEL to solve the UWC problem in this application to the real case.